Legal Problems on Regional Head Election during COVID-19 Pandemic in Indonesia - Nila Nargis; M. Iwan Satriawan (Constitutionale, 2021)
The problem of the Covid-19 disease outbreak in Indonesia is of particular concern. This epidemic caused political and economic shocks to the state administration system. The problems that exist are related to the implementation of the Regional Head Election during the pandemic. This paper aims to find out the legal issues of regional head elections during a pandemic. The method used is the normative juridical method. The results of this paper show that the legal problem lies in the aspect of regulatory implementation. The government must continue to work hand in hand with handling the covid-19 outbreak and still prioritize the health of Indonesian citizens. Of course, the implementation of Regional Head Election does not violate the law based on Regulation in Lieu of Law No.2 of 2020 concerning the third amendment to Law No.1 of 2015 concerning Regional Head Election.